MicroRNAs-29a/b/c regulate early growth response 2 (Egr2) by mPer1. Issue 4 (4th July 2017) - Ying, Junjie; Wang, Yuhui; Hou, Wang; Li, Xiaoxue; Jiang, Zhou; Liu, Yanyou; Ding, Lu; Yang, Shuhong; Wang, Zhengrong
Abstract: The circadian rhythm is one of the basic systems in an organism. It helps the organism maintain harmony with the daily changes of the external environment to ensure proper physiological activities. Previous studies from our laboratory have indicated that the miR-29a/b/c can bind to the circadian clock gene hPer1 at the 3 ′UTR region and regulate its mRNA and protein expression, affecting various organismal physiological processes. Meanwhile, it has been reported that the circadian gene Per plays a role in the regulation of the early growth response gene Egr2, which plays an important role during midbrain development. Here, we confirmed that miR-29a/b/c regulates Egr2 function through mPer1 binding, which elucidates a novel connection between mPer1 and Egr2.